2022
DOI: 10.1177/21582440221078016
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Learning as a Pathway to Strengthening Motivation and Improving Achievement in an EFL Classroom

Abstract: The importance of applying cooperative learning and aiming toward an increase in motivation to maximize the effectiveness of the learning process has not sparked an intense research interest in the Bosnian EFL context. Thus, the current study, conducted among 211 high-school participants, explores the impact of gender and grade level on students’ cooperative learning and motivation for EFL learning and aims to determine whether any cooperative learning components are significant predictors of students’ motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 63 publications
3
17
1
Order By: Relevance
“…The hypotheses that cooperative learning positively predicts students’ EFL motivation and that EFL positively predicts students’ EFL achievement were also supported. These findings are in line with other studies that previously demonstrated the significant effects of cooperative learning on students’ motivation (Alghamdy, 2019; Bećirović et al, 2022; Gashti, 2021; S. H. J. Liu & Lan, 2016; Lynn Brown, 2021; Moghaddam & Heidari, 2018; Nazari et al, 2021; Neo et al, 2012; Ning & Hornby, 2014; Quinn, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…The hypotheses that cooperative learning positively predicts students’ EFL motivation and that EFL positively predicts students’ EFL achievement were also supported. These findings are in line with other studies that previously demonstrated the significant effects of cooperative learning on students’ motivation (Alghamdy, 2019; Bećirović et al, 2022; Gashti, 2021; S. H. J. Liu & Lan, 2016; Lynn Brown, 2021; Moghaddam & Heidari, 2018; Nazari et al, 2021; Neo et al, 2012; Ning & Hornby, 2014; Quinn, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…The study focused exclusively on the investigation of extrinsic and intrinsic motivation. In light of the correlation and evaluation, it is found that the learners are slightly more extrinsically motivated to learn English, which is in line with previous studies investigating this specific learning context (Ahmetović & Dubravac, 2021;Bećirović, Dubravac, & Brdarević-Čeljo, 2022). The reason could be the fact that English is a world language, and the ability to communicate it properly is considered a required skill in this country Dedović-Atilla & Dubravac, 2022).…”
Section: Discussion and Recommendationsupporting
confidence: 85%
“…Thus, motivation for its learning is the topic that needs to be explored. Previous studies conducted in this context showed that students are highly motivated to learn English (Ahmetović & Dubravac, 2021;Bećirović, Dubravac, & Brdarević-Čeljo, 2022;Latić & Dubravac, 2019). However, while both extrinsic and intrinsic motivation seems to be high, extrinsic dominates in this learning setting, as illustrated by Ahmetović, Bećirović and Dubravac (2020).…”
Section: Hussain Et Al (mentioning
confidence: 87%
“…These assessment activities were often conducted in group and collaborative forms. These forms are conducive in nurturing a positive attitude toward and an interest in participating in these activities (Bećirović et al, 2022; Jagger, 2013). These activities then offer a good learning experience to the learners and improve their enjoyment of the class (Alamdari & Ghani, 2022; C.…”
Section: Discussionmentioning
confidence: 99%